The Measurement of Learning in the Museum - Donald, Janet (Canadian Journal of Education/Revue canadienne de l’éducation, 1991)
With increased interest in the educational role of museums, learning in museums and its measurement have become important questions. The most frequently used measures in museums are attracting power and holding power; but measures used by educators are of time on task, knowledge gained, thinking and problem- solving skills, motivation or attitudes, and creativity. The objective of this study was to delineate and to evaluate measures of learning applicable to museum experience. Different kinds of museums—fine arts, natural history, science, and centres of interpretation—promote different kinds of learning, but all pay attention to specific measures of learning: knowledge gain and thinking. Plus on s’intéresse au rôle éducatif des musées, plus l’apprentissage dans les musées et les instruments de mesure connexes prennent de l’importance. Les critères de mesure souvent retenus dans les musées sont le pouvoir d’attraction et de rétention; les éducateurs, eux, considèrent plutôt le temps consacré à la tâche, les connaissances acquises, la pensée et l’aptitude à résoudre des prob- lèmes, la motivation ou les attitudes et la créativité. L’étude présentée dans cet article visait à distinguer et à évaluer les mesures de l’apprentissage applicables à l’expérience muséale. Les divers types de musées—musées des beaux-arts, de sciences naturelles, des sciences et de la technologie, centres d’interprétation— privilégient différents types d’apprentissage, mais tous accordent de l’importance à deux critères de mesure, l’acquisition des connaissances et la pensée.